Bacteriophage cocktail as a substitute for antimicrobials in companion animal dermatology - Yhann Pool Angelo Vallenas-Sánchez; María Fernanda Bautista-Valles; Fabiana Llaque-Chávarri; Martin Enrique Mendoza-Coello (Journal of the Selva Andina Animal Science)
The present study focuses on the use of phage cocktails as a substitute for antibiotics in companion animal dermatology. For this purpose, a systematic search was carried out in the Scopus database, with the search criteria: "veterinary" and "bacteriophage" and "dermatology" in article title, abstract and keywords during the period 2010-2021. Seven in vitro studies and one in vivo study in companion animals, for which those carried out in laboratory animals were added. In this review, the use of non-transducing lytic phage cocktails as therapeutics for pyodermas is discussed and projected, as well as the resistance to phages and the strategies to overcome it, the comparison with antibiotics, the use of cocktails in other animal species, as well as the use of individual phages and cocktails in veterinary dermatology, and autochthonous phages as a strategy when phage collections from previous studies do not have the desired effects. It is concluded that non-transducing lytic autophage cocktails are an alternative against antimicrobial resistance in companion animal dermatology. Finally, it is recommended to compare the use of these cocktails with other antibiotic substitutes and evaluate their possible synergism to reduce pathogenic bacteria on the skin.